Partnership, policy and politics: Initial teacher education in England under New Labour - Furlong, J; McNamara, O; Campbell, A; Howson, J; Lewis, S (2008)
Over the last 15 years, initial teacher education in England has been established as a national system, closely controlled by the government. One of the consequences of this move is that teacher education is now intimately bound up with changing national politics and policy priorities which reach down into the finest of detail of provision. In this paper, we focus on the way in which politics and policy have impacted on one of the defining features of teacher education provision in England - that of 'partnership'. In particular we examine the way in which the concept and practice of partnership has been transformed in line with New Labour's 'Third Way' politics. In order to do this, we reflect on our recent evaluation of the National Partnership Project, an initiative established by the Training and Development Agency for Schools to increase the quality and quantity of schools' involvement in initial teacher education.